Between Memory and Ethics: Real Human-Educators Transformed into Virtual Human-Educators - Castro, Michele Marta Moraes; Maciel, Cristiano (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
This article examines the ethical dilemmas that arise from the transformation of real human-educators into virtual human-educators using artificial intelligence, particularly in posthumous contexts. Based on the project “Dados Além da Vida” (DAVI – Data Beyond Life), it investigates the boundaries between memory and technology in the recreation of deceased educators using generative models. The study explores how digital traces, such as voice, scholarly productions, and images, are mobilized to simulate presence and interaction, raising tensions between memory and ethics. Considering the current capabilities of Artificial Intelligence, the article discusses whether it is ethically acceptable to convert the memory of real humaneducators into virtual human-educators, and what implications this entails.